DEVELOPMENT POLITICS OF DALIHAN NA TOLU IN THE SOCIAL PERSPECTIVE OF BATAK ANGKOLA PEOPLE - Harahap, Suheri; Alfikri, Muhammad (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
This study aims to describe the development politics of Dalihan Na Tolu in the social perspective of the Angkola Batak indigenous people. Humanist political philosophy in South Tapanuli is very basic to be used as motivation for the younger generation because the beginnings of politics stem from various views on the meaning of power and how life situations are in various countries, as well as the times. This study uses a descriptive qualitative research method. Data collection was carried out by literature study, observation, document analysis, and interviews. The results of the study show that South Tapanulis is an area where the Islamic religion and Angkola culture are very strong with the kinship system "dalihan na tolu". Dalihan Na Tolu's local cultural conception with the view of life of noble ancestors in the social order of living together, working together, shoulder to shoulder, rap tu ginjang (rising to the highest level/peak of success), rap tu toru (failure/falling together -sama), marsipature junglea be (to build their own hometown). Humanist political philosophy in South Tapanuli is very important to be used as motivation for the younger generation, because the beginnings of politics stem from various views on the meaning of power and how the situation of life is in various countries and so is the development of the times. Politics is the way the existing society sees itself in managing its life so that it is better. South Tapanulis is an area that has a very strong Islamic religion and Angkola cultural customs with a kinship system "dalihan na tolu". It is an undeniable fact that the political tradition that has often been practiced so far in seizing power is by relying on the power of capital (hepeng) or in the form of praxis by using the 'dawn attack' strategy (Money politic). It is this kind of democratic character that we will fight against. Can people who have strong religion and customs fight the power of capital? It is time for direct local elections to be able to change the paradigm of people's thinking from capital-oriented to cultural-oriented, towards a strong civilization. This spirit is a challenge for the sons and daughters of South Tapanuli who want to share their views with the conception of a culture of political resistance "marsialap ari" as a conception of local culture with the view of life of noble ancestors in a social order living together, working together, shoulder to shoulder, rap tu ginjang (rising to the highest level/peak of success), rap tu toru (failure/falling together), marsipature junglea be (building each other's hometown).